Про динаміку відкритої економічної системи за наявності монополістів і фінансових зобов’язань - Makhort, Andrii (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
An investigation was conducted of an open economy consisting of insatiable consumers. Some consumers can produce own goods to gain a profit while other consumers obtain an external support. The equilibrium is of a Walrassian type. The model takes into account an economy with monopolies and financial obligations of its subjects. The financial obligations lead to the capital redistribution between subjects of the economy. A formation of consumers' preferences depends on the financial obligations. There exists an equilibrium of such an economy. Obtained equilibrium values of model characteristics agree on an acceptable level of the consumption satisfaction of all economy subjects. The values of the capital redistribution are determined at which the levels of the consumption belong to the defined set of values. Based on the evolution of the financial obligations, the description of economy dynamics was proposed.